The Effect of Leadership and Organizational Culture on Work Motivation and Their Implications on Teacher Performance - Angela, Lia; Ekawarna, Ekawarna; Sulistiyo, Urip; Sofyan, Hendra; Sarmigi, Elex (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
The purpose and objective of this research is to see how the factors of leadership and organizational culture directly affect teacher performance. The sample is the teachers of SMAN 4 Kerinci totaling 72 people, instrument is questionnaire. The collected data was then analyzed by path analysis method with the help of SMARTPLS 3.0 software. The results of this study found that leadership factors and organizational culture affect teacher performance both directly and indirectly which are mediated by work motivation. The effect of work motivation on the influence of leadership and organizational culture on teacher performance is partial mediation.